Resistance to rifampicin: a review - Goldstein, Beth P (Journal of antibiotics, 2014)
Resistance to rifampicin (RIF) is a broad subject covering not just the mechanism of clinical resistance, nearly always due to a genetic change in the β subunit of bacterial RNA polymerase (RNAP), but also how studies of resistant polymerases have helped us understand the structure of the enzyme, the intricacies of the transcription process and its role in complex physiological pathways. This review can only scratch the surface of these phenomena. The identification, in strains of Escherichia coli , of the positions within β of the mutations determining resistance is discussed in some detail, as are mutations in organisms that are therapeutic targets of RIF, in particular Mycobacterium tuberculosis . Interestingly, changes in the same three codons of the consensus sequence occur repeatedly in unrelated RIF-resistant (RIF r ) clinical isolates of several different bacterial species, and a single mutation predominates in mycobacteria. The utilization of our knowledge of these mutations to develop rapid screening tests for detecting resistance is briefly discussed. Cross-resistance among rifamycins has been a topic of controversy; current thinking is that there is no difference in the susceptibility of RNAP mutants to RIF, rifapentine and rifabutin. Also summarized are intrinsic RIF resistance and other resistance mechanisms.